Description of a new genus of spider beetle (Coleoptera: Ptinidae) from South Africa - Akotsen-Mensah, Clement; Philips, T. Keith (Zootaxa, 2009)
Pocapharaptinus gen. nov. and eight new species, P. müllerae sp. nov., P. harrisoni sp. nov., P. akotsenorum sp. nov., P. capensis sp. nov., P. soutpanensis sp. nov., P. lachnos sp. nov., P. aboakyer sp. nov., and P. acanthus sp. nov. are described from South Africa. The genus is distinguished by the pronotal surface being densely covered with flocculent, wooly, tan colored setae obscuring the cuticular surface except anteriomedially, where the bare cuticle is variably triangular in shape. All species are illustrated, described, diagnosed and an identification key provided. The biogeography and relationships of this genus to other Ptinidae are also discussed.